Yuridis Normatif Doa Lintas Agama dalam Kehidupan Multikultural - Ali Ridho (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
This paper raises a culture that develops at the level of multicultural society, which is a gathering event, having du'a together among adherents of religion. In this paper, the writer tries to take some references and then make a dialogue between those references, means the Qur'an itself, the book of interfaith fiqh and the MUI fatwa. Such an activity would be highly controversial between the pros and the cons. In the view of its own normative path, the Qur'an clearly states that non-Muslims will be rejected and in digression, although this context does not explain about du'a together. While the fiqh of interreligions, because the basic is the inclusive pluralist theology and not Islamic faith (aqidah Islam). So it is clear, if the basic of this book is pluralism, this book is an understanding of pluralism, or an understanding of inclusiveness and openness and understanding that a part of other religion has a path of truth and savety that is not as complete as the religion he embraces. Therefore, according to this book, this tradition is a natural thing and not problematic. While the MUI itself in its fatwa provides legal values and procedures of praying that are allowed and not allowed.